Holocene biogeography of Tsuga mertensiana and other conifers in the Kenai Mountains and Prince William Sound, south-central Alaska. (April 2017) - Anderson, R Scott; Kaufman, Darrell S; Berg, Edward; Schiff, Caleb; Daigle, Thomas
Several important North American coastal conifers – having immigrated during the Holocene from the southeast – reach their northern and upper elevation limits in south-central Alaska. However, our understanding of the specific timing of migration has been incomplete. Here, we use two new pollen profiles from a coastal and a high-elevation site in the Eastern Kenai Peninsula–Prince William Sound region, along with other published pollen records, to investigate the Holocene biogeography and development history of the modern coastal Picea (spruce)– Tsuga (hemlock) forest. Tsuga mertensiana became established at Mica Lake (100 m elevation, near Prince William Sound) by 6000 cal. BP and at Goat Lake (550 m elevation in the Kenai Mountains) sometime after 3000 years ago. Tsuga heterophylla was the last major conifer to arrive in the region. Although driven partially by climate change, major vegetation changes during much of the Holocene are difficult to interpret exclusively in terms of climate, with periods of slow migration alternating with more rapid movement. T. mertensiana expanded slowly northeastward in the early Holocene, compared with Picea sitchensis or T. heterophylla . Difficulty of invading an already established conifer forest may account for this. We suggest that during the early Holocene, non-climatic factors as well as proximity to refugia, influenced rates of migration. Climate may have been more important after ~2600 cal. BP. Continued expansion of T. mertensiana at Goat Lake at the Medieval Climate Anomaly (MCA)–'Little Ice Age' ('LIA') transition suggests warm and wet winters. But expansion of T. mertensiana at both sites was arrested during the colder climate of the 'LIA'. The decline was more extensive at Goat Lake, where climatic conditions may have been severe enough to reduce or eliminate the T. mertensiana population. T. mertensiana continued its expansion around Goat Lake after the 'LIA'.